Understanding the interaction between biomacromolecules and their influence on forward osmosis process - Arkhangelsky, Elizabeth (2016)
This paper presents studies on the interactions and effects of biomacromolecules compounds on forward osmosis (FO) membrane performance. Individual components and a combination of various organic substances such as bovine serum albumin (BSA), dextran, sodium alginate and xanthan gum were used as model feeds and tested for their influences on FO performance with the active layer of the FO hollow fiber membrane facing the feed solution (AL-FS). The interactions between foulants were examined by using fluorescence spectroscopy, rotational rheometry and laser doppler micro-electrophoresis techniques. For a system containing combined organic foulants, it was found that viscosity was not the dominant factor governing FO membrane fouling as the decrease in viscosity did not always result in less fouling. The effect of divalent cations on the FO fouling behavior was also studied by adding CaCl2. The presence of calcium ions has exacerbated the flux decline, this occurred particularly for any combined organic foulants containing alginate, due to intermolecular bridging among alginate molecules. It is interesting to note that combined BSA + alginate caused moderate flux decline, while BSA and alginate alone did not cause any observable water flux loss. The (BSA + alginate) fouling became more severe with the presence of calcium ions.